Occurrence of lipid peroxidation in repeatedly used cooking oil in Kelantan - Ramli, Nurul Syahmi Mohd (Pusat Pengajian Sains Kesihatan, Universiti Sains Malaysia, 2005)
Lipid peroxidation (LPO) is the oxidative deterioration of lipids containing any number of carbon - carbon double bonds. It is a chain reaction providing a continuous supply of free radicals that initiate further peroxidation. The purpose of this study is to standardize a simple and cheap method for estimating oxidation of lipids in the cooking oil samples. The other objective of this study is to compare the occurrence of oxidation of lipids in fresh cooking oil and repeatedly used cooking oil samples. The reused oil samples are obtained from four stalls who were selling fried bananas. They were supplied with EKONOMI palm oil packs or pouches to be used on daily basis. The oil has been used solely for deep - frying the bananas. The banana hawkers were instructed to keep using the oil left at the end of the day for the next day business and they were allowed to refill the oil with the fresh one when needed. The collection of the oil was on daily basis for 7 consecutive days followed by the 14th day, 21 81 day and 30th day following the reusage. Our study has shown that the malondialdehyde concentration in the reused oil at all four banana stalls was increased during the period (30 days) of our study. The results have shown that the increased malondialdehyde concentration in the reused oil following rancidity were due to many factors. The factors which caused an increased amount of malondialdehyde concentration in the reused oil were air pollution, dirty utensils, length oftime period that the oil has been used, an infrequent replacement of reused oil with fresh one and the locality of the stall. The pH of the reused oil samples was also been measured. Most of the reused oil samples from all stalls showed a decrease of pH throughout the study period. The reduced in pH showed that the reused oil samples had become more acidic in comparison to the fresh oil samples. This might have enhanced malondialdehyde formation. Future studies, in animal models following feeding of oil samples might open new horizons in the ill - health effects of such oil in human population. xi